MULTIPHASE FLOW REGIME CHARACTERISTICS OF AIR AND WATER IN MICROCHANNEL - LEE, ROGER JUN SHEN (2023)
Earth’s surface temperature has been increasing for the past decades due to the industrial revolutions, causing high emission of greenhouse gas (GHG) to the surroundings which cause global warming.